Effect Of Profitability, Liquidity And Sales Level On Income Growth With Company Size As Moderated Variables In Registered Consumption Sector Manufacturing Companies In Indonesia Exchange For 2016-2018: Pengaruh Profitabilitas, Likuiditas Dan Tingkat Penjualan Terhadap Pertumbuhan Pendapatan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Sektor Konsumsi Terdaftar Di Bursa Indonesia Tahun 2016-2018 - Elisa Widya M; Eny Maryanti (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of profitability, liquidity and sales level on profit growth with company size as a moderating variable in consumer sector manufacturing companies listed on the Indonesian stock exchange for the period 2016-2018. Previous studies have shown different results. Research needs to be done again to examine the effect of the three variables on profit growth by adding company size as a moderating variable. The population of this study is the consumer sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2018 period totaling 38 companies. Based on the purposive sampling criteria, there were 15 companies that met the research criteria. This study uses data analysis testing SmartPLS 3 . The results showed that profitability, liquidity and sales levels had no effect on profit growth. Company size as a moderating potential variable on the effect of profitability, liquidity and sales level on profit growth.